The Statue of Apollo Smintheus by Scopas and the Monumental Policy of the Satrap Artabazos - Corso, Antonio (Actual Problems of Theory and History of Art, 2019)
In this article, the surviving fragment of Scopas’ statue of Apollo Smintheus in Troad is considered.The sacred landscape in which the statue was set up, the history of this sanctuary and its possible political patronage are analyzed. The colossal masterpiece may have been promoted by Artabazos, the satrap of Hellespontine Phrygia of the middle of the 4th century B.C. This satrap may have promoted also the Eros by Praxiteles at Parion, the Paris by Euphranor at Parion and the Apollo Sauroktonos by Praxiteles at Apollonia ad Rhyndacum. He may have been introduced to important workshops of sculptors based in Athens thanks to his alliance with the Athenian general Chares. The philosopher Eudoxos settled in Cyzikos may have provided the philosophical background of this art of pleasure.
Keywords: Apollo Smintheus; Chryses; Chryseis; Scopas; Artabazos; Praxiteles; Euphranor; Chares; Eudoxos of Cnidus